Pre-Service Teachers’ Perspectives on Their Preparedness to Use Technology in Classrooms in the United Arab Emirates: A Qualitative Approach - Mohebi, Laila (2019)
This study is aimed at understanding United Arab Emirates (UAE) pre-service teachers’ perspectives on their preparedness to use technology for future classroom practices, as well as their instructors’ perspectives on pre-service teachers’ preparedness to use technology for future classroom practices. It also looks into the pre-service teachers and instructors’ suggestions for future action plans to maximize the preparedness and the factors that influence the acquisition of knowledge and skills regarding technology integration in the classroom. In addition, the study is based on the Technological Pedagogical and Content Knowledge (TPACK) model as a framework to assess and reflect on the technology integration skills of pre-service teachers. This study was conducted in three selective universities in the United Arab Emirates (UAE) by use of a qualitative approach from interviews with 12 pre-service teachers and 6 instructors. It used thematic analysis for the interviews to understand the pre-service teachers´ and their instructors´ perspectives on TPACK variables. In addition, thematic analysis was used for suggestions and recommendations. The analysis showed that in general, pre-service teachers are confident when it comes to their TPACK capabilities. Moreover, results indicated that the most significant factor that influenced the acquisition of knowledge and skills regarding information and communication technology (ICT) integration in the classroom was practical experiences in schools. However, the analyses of the interviews of both pre-service teachers and instructors showed that there were some challenges and points for improvement to be considered.